New mtDNA Association Model, MutPred Variant Load, Suggests Individuals With Multiple Mildly Deleterious mtDNA Variants Are More Likely to Suffer From Atherosclerosis - Piotrowska-Nowak, Agnieszka; Elson, Joanna L.; Sobczyk-Kopciol, Agnieszka; Piwonska, Aleksandra; Puch-Walczak, Aleksandra; Drygas, Wojciech; Ploski, Rafal; Bartnik, Ewa; Tonska, Katarzyna (Frontiers in Genetics, 2019)
The aetiology of common complex diseases is multifactorial, involving both genetic and environmental factors. A role for mitochondrial dysfunction and mitochondrial DNA (mtDNA) variation has been suggested in the pathogenesis of common complex traits. The aim of this study was to investigate a potential role of mtDNA variants in the development of obesity, diabetes and atherosclerosis in the Polish population. Whole mtDNA sequences from 415 Polish individuals representing three disease cohorts and a control group were obtained using high-throughput sequencing. Two approaches for the assessment of mtDNA variation were applied, traditional mitochondrial haplogroup association analysis and the mutational or variant load model using the MutPred pathogenicity prediction algorithm for amino acid substitutions in humans. We present a possible association between mildly deleterious mtDNA variant load and atherosclerosis that might be due to having more than one likely mildly deleterious non-synonymous substitution. Moreover, it seems largely dependent upon a few common haplogroup associated variants with MutPred score above 0.5.